Correction: A study of the depth and size of concave cube Au nanoparticles as highly sensitive SERS probes. Issue 15 (3rd April 2017) - Romo-Herrera, J. M.; González, A. L.; Guerrini, L.; Castiello, F. R.; Alonso-Nuñez, G.; Contreras, O. E.; Alvarez-Puebla, R. A.
Abstract : Correction for 'A study of the depth and size of concave cube Au nanoparticles as highly sensitive SERS probes' by J. M. Romo-Herrera et al., Nanoscale, 2016, 8, 7326–7333.